2014
DOI: 10.1016/j.jadohealth.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Masculine Boys, Feminine Girls, and Cancer Risk Behaviors: An 11-Year Longitudinal Study

Abstract: Objective Cancer risk behaviors often begin in adolescence and persist through adulthood. Tobacco use, indoor tanning, and physical inactivity are highly prevalent, socially patterned cancer risk behaviors, and their prevalence differs strongly by sex. It is therefore possible that these behaviors also differ by gender expression within the sexes due to social patterning. Methods We examined whether 5 cancer risk behaviors differed by childhood gender expression within the sexes and whether patterns of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Evidence is accumulating that these messages carry with them health risks in myriad domains. [9][10][11][12]32 With the present study, it is clear that conformity to masculinity ideals confers risk of elevated BMI in both sexes and, for males in particular, more rapid BMI gains in adolescence. While our study examined a wide range of known predictors of BMI in youth, our results indicated that these exposures accounted for a relatively small proportion of the pronounced gender-expression group differences in BMI.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Evidence is accumulating that these messages carry with them health risks in myriad domains. [9][10][11][12]32 With the present study, it is clear that conformity to masculinity ideals confers risk of elevated BMI in both sexes and, for males in particular, more rapid BMI gains in adolescence. While our study examined a wide range of known predictors of BMI in youth, our results indicated that these exposures accounted for a relatively small proportion of the pronounced gender-expression group differences in BMI.…”
Section: Discussionsupporting
confidence: 50%
“…21 Furthermore, recent evidence implicates societal pressures on young people to conform to socially accepted expressions of masculinity and femininity in a range of health damaging behaviors, 9-11 including weightrelated behaviors. 11,12,32 Nevertheless, to our knowledge, this is the first prospective cohort study examining the relationship between gender expression and BMI in adolescence. Our findings indicate that socially assigned gender expression is a powerful predictor of BMI.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…18,19 Health behaviors, especially those related to appearance, may be a way of embodying or establishing adherence to gender norms. 17,20,21 Because appearance ideals for girls and women center on thinness, whereas appearance ideals for boys and men focus on muscularity, the likelihood of using products to modify weight, shape, or appearance may be associated with overall gender differences in conformity to femininity and masculinity norms. [22][23][24] Laxative use to maintain or lose weight, particularly among girls and women, may be connected to greater conformity to appearance norms associated with femininity, and muscle-building product use, particularly among boys and men, may be connected to greater conformity to appearance norms associated with masculinity.…”
mentioning
confidence: 99%